PENGARUH KONDISI HIPOKSIA HIPOBARIK TERHADAP PEMANJANGAN WAKTU TRANSPORT MUKOSILLIER HIDUNG PADA KADET CALON PENERBANG - , MAHATMA SUTYA BAWONO, Dr.Luh Putu Lusy Sp.THT-KL,M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Hypoxia hypobaric condition is a condition that is often experienced, especially by people who often work at heights. Some conditions that occur at high altitude can cause changes in pressure, temperature, and humidity. Recurrent acute hypoxia hypobaric often be experienced by the pilot, especially when they had to undergo the hypobaric chamber training procedure which regularly held every two years. The purpose of this study is to assess the influence hypoxia hypobaric condition on the mucociliary movement on aviators.This research design is non-blinding randomized controlled trial studies to compare the effects of interventions among groups that undergo hypobaric chamber training with the control group. The statistical test used was Wilcoxon test, given the level of significance. Subject that has fulfilled the inclusion and exclusion criteria established saccharin tests. All subject enter the hypobaric chamber with the height of sea level rise to 5000 ft, back down to sea level, then up to 18 000 ft. At 18 000 ft above sea level all subject take off their oxygen mask, and saccharin tests being perform again,then all subject up to 25.000 ft to proceed with the training procedure. In the control group saccharin test was performed twice. The result of this research was the level of significance in the group of samples before and after treatment was 0,001,whereas the comparison group was 0.002. The level of significance between the comparison group and treatment group after treatment was 0,001. Hypoxia caused by hypobaric condition may lead to an extension of mucosilliary clearance time in the nose which mean that nasal mucocilliary speed is decreasing.